Ph Salival y su relación con la Ortodoncia fija de los y las Estudiantes de la Universidad Nacional de Loja de la Modalidad de Estudios Presencial de 18 a 30 años de edad, periodo mayo - julio 2014. - Gaona González, Lenin Bladimir (2014)
The present study of descriptive cross-sectional kind, it was aimed in the salivary pH of carriers fixed orthodontic students mode of classroom studies by the Loja National University from 18 to 30 years old, in the period May-July 2014. The used technologies were the observation and clinical diagnosis of the oral cavity. The medical odontology history was used as an instrument of compilation date to assess or for evaluating the study variables: Carrying patients with fixed orthodontic salivary pH and also using paper strips to measure salivary pH (litmus), which allowed us to identify the status of the oral environment in patients with fixed orthodontic appliances. The collection instrument data was applied to 894 students, who 91 involved as subjects because they met the inclusion criteria. The results showed which 10.2% of the total population has fixed orthodontics; by gender, 49.4% were male and 50.6% female gender. In the male salivary pH more frequently with 62.2% normal and obvious alteration is salivary pH acid with 20.2%. While in females the greatest alteration occurs in the basic pH with 21.8% Keywords: fixed orthodontics, salivary pH.